Transformasi Emosi melalui Dzikir dan Shalat dalam Konteks Pendidikan Islam: Studi Kualitatif tentang Penanganan Stres dan Kecemasan - Agus Nurkholiq; Nenden Maryati (Asatidzuna | Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to examine the role of dhikr and prayer in emotional transformation, particularly in managing stress and anxiety, and its relationship with Islamic education. The research employs a qualitative method with a phenomenological approach, involving in-depth interviews with individuals actively practicing dhikr and prayer. The findings indicate that dhikr and prayer have a significant impact on reducing levels of stress and anxiety by providing inner peace and emotional stability. These findings also highlight the importance of Islamic education in fostering healthy spiritual habits, which in turn support psychological well-being. Integrated Islamic education with practices of dhikr and prayer can be an effective strategy in addressing emotional challenges and enhancing the quality of life. This study suggests further implementation in the Islamic education curriculum to optimize the spiritual and emotional benefits of dhikr and prayer.